Active NET formation in Libman-Sacks endocarditis without antiphospholipid antibodies: A dramatic onset of systemic lupus erythematosus - Daniel Appelgren; Charlotte Dahle; Jasmin Knopf; Rostyslav Bilyy; Volodymyr Vovk; Pia C. Sundgren; Anders A. Bengtsson; Jonas Wetterö; Luis E. Muñoz; Martin Herrmann; Anders Höög; Christopher Sjöwall (Taylor & Francis Group, 2018)
Although neutrophil extracellular traps (NETs) have been highlighted in several systemic inflammatory diseases, their clinical correlates and potential pathological role remain obscure. Herein, we describe a dramatic onset of systemic lupus erythematosus (SLE) with clear-cut pathogenic implications for neutrophils and NET formation in a young woman with cardiac (Libman-Sacks endocarditis) and central nervous system (psychosis and seizures) involvement. Despite extensive search, circulating antiphospholipid autoantibodies, a hallmark of Libman-Sacks endocarditis, could not be detected. Instead, we observed active NET formation in the tissue of the mitral valve, as well as in the circulation. Levels of NET remnants were significantly higher in serially obtained sera from the patient compared with sex-matched blood donors (p = .0011), and showed a non-significant but substantial correlation with blood neutrophil counts (r = 0.65, p = .16). The specific neutrophil elastase activity measured in serum seemed to be modulated by the provided immunosuppressive treatment. In addition, we found anti-Ro60/SSA antibodies in the cerebrospinal fluid of the patient but not NET remnants or increased elastase activity. This case illustrates that different disease mechanisms mediated via autoantibodies can occur simultaneously in SLE. NET formation with release of cytotoxic NET remnants is a candidate player in the pathogenesis of this non-canonical form of Libman-Sacks endocarditis occurring in the absence of traditional antiphospholipid autoantibodies. The case description includes longitudinal results with clinical follow-up data and a discussion of the potential roles of NETs in SLE.